1985
DOI: 10.1002/cne.902340202
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the rostral thalamus in the rat: Evidence for connections to layer I of visual cortex

Abstract: The present study demonstrates the organization of a thalamocortical projecting system which terminates within layer I of the visual cortex in the hooded rat. Horseradish peroxidase (HRP) injections restricted to layer I resulted in retrograde labeling of large and medium-sized multipolar and fusiform neurons that are located within the ventromedial (VM) nucleus and a dorsomedial subunit of the ventral anterolateral nucleus (VAL). Retrograde cellular labeling also occurs within the anteromedial nucleus (AM) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 80 publications
2
13
0
1
Order By: Relevance
“…The projection patterns described are thus arranged into two large thalamocortical circuits: 1) topographic projection of thalamic core cells > middle cortical layers > superficial layers > deep layers, with reciprocal topographic feedback from layer VI back to both the core cells and to the overlying portion of nucleus reticularis; 2) matrix cells projecting nontopographically to layer I and receiving projections back from layer V, without interposed nucleus reticularis projections. Evidence suggests that the repeating thalamocortical, cortico-cortical, and corticothalamic projection patterns hold not only for primary sensory areas including VPM/VPL, LGd, and MGv to layer IV, and Pom, LP/Pul, and MGm to layer I of somatosensory, visual and auditory cortices, respectively (Killackey and Ebner, 1972;Ryugo and Killackey, 1974;Ribak and Peters, 1975;Herkenham, 1980;Kelly and Wong, 1981;Swadlow, 1983;Rieck and Carey, 1985;Herkenham, 1986;Jensen and Killackey, 1987;Winer and Larue, 1987;Scheel, 1988;Conley and Diamond, 1990;Rouiller and Welker, 1991;Bourassa and Deschenes, 1995;Huang and Winer, 2000), but also for a wide array of thalamic nuclei, intralaminar and nonintralaminar alike (Jones and Hendry, 1989;Rausell et al, 1992;Molinari et al, 1994;Molinari et al, 1995;Kuroda et al, 1998;Mitchell and Cauller, 2001;Rauschecker et al, 1997;Jones, 1998;Reep and Corwin, 1999;Linke and Schwegler, 2000;Jones, 2001)). For those cortical areas not receiving topographic projections from thalamus, the extensive topography-preserving cortico-cortical projections from superficial layers to recipient middle layers with reciprocal projections from the target's deep layers back to the source's superficial layers, may subserve a related function …”
Section: Anatomical Architecture Of Thalamocortical Circuitsmentioning
confidence: 99%
“…The projection patterns described are thus arranged into two large thalamocortical circuits: 1) topographic projection of thalamic core cells > middle cortical layers > superficial layers > deep layers, with reciprocal topographic feedback from layer VI back to both the core cells and to the overlying portion of nucleus reticularis; 2) matrix cells projecting nontopographically to layer I and receiving projections back from layer V, without interposed nucleus reticularis projections. Evidence suggests that the repeating thalamocortical, cortico-cortical, and corticothalamic projection patterns hold not only for primary sensory areas including VPM/VPL, LGd, and MGv to layer IV, and Pom, LP/Pul, and MGm to layer I of somatosensory, visual and auditory cortices, respectively (Killackey and Ebner, 1972;Ryugo and Killackey, 1974;Ribak and Peters, 1975;Herkenham, 1980;Kelly and Wong, 1981;Swadlow, 1983;Rieck and Carey, 1985;Herkenham, 1986;Jensen and Killackey, 1987;Winer and Larue, 1987;Scheel, 1988;Conley and Diamond, 1990;Rouiller and Welker, 1991;Bourassa and Deschenes, 1995;Huang and Winer, 2000), but also for a wide array of thalamic nuclei, intralaminar and nonintralaminar alike (Jones and Hendry, 1989;Rausell et al, 1992;Molinari et al, 1994;Molinari et al, 1995;Kuroda et al, 1998;Mitchell and Cauller, 2001;Rauschecker et al, 1997;Jones, 1998;Reep and Corwin, 1999;Linke and Schwegler, 2000;Jones, 2001)). For those cortical areas not receiving topographic projections from thalamus, the extensive topography-preserving cortico-cortical projections from superficial layers to recipient middle layers with reciprocal projections from the target's deep layers back to the source's superficial layers, may subserve a related function …”
Section: Anatomical Architecture Of Thalamocortical Circuitsmentioning
confidence: 99%
“…Despite numerous descriptions of the rat thalamus Mehler, 1976, 1985;Jones, 1985;Rieck and Carey, 1985;Paxinos and Watson, 1986;Sawyer et al, 1989;Deniau and Chevalier, 1992;Swanson, 1992;Price, 1995), there is no consistency in the delineation of the rat ventral thalamus. Therefore, for the most part, we have relied upon the thalamic parcellation presented in the atlas of Paxinos and Watson (1986).…”
Section: Delineation Of Rat Val and Vmmentioning
confidence: 99%
“…On the basis of our own analysis of a Nissl-and AChE-stained series through the rat thalamus, we were unable to determine a boundary between the VA and the VL. Therefore, we have adopted the designation of this region as the VAL (Faull and Mehler, 1976;Rieck and Carey, 1985;Sawyer et al, 1989Sawyer et al, , 1991Sawyer et al, , 1994. We found that the primary nigral projection was to the rostromedial part of the VAL and VM.…”
Section: Comparative Organization Of Nigrothalamocortical Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work has demonstrated first, that not only the ventromedial nucleus, but also some other thalamic nuclei, project predominantly to the first layer. These nuclei are named "paralamellar" (Rieck and Carey 1985;Herkenham 1986). Secondly, it was found that the intralaminar nuclei project diffusely to the cortex, but only to deep layers (review in Herkenham 1986).…”
Section: Subcortical Efferents Ot the Isocortexmentioning
confidence: 99%